2002
DOI: 10.1046/j.1523-1747.2002.01806.x
|View full text |Cite
|
Sign up to set email alerts
|

Defolliculated (Dfl): A Dominant Mouse Mutation Leading to Poor Sebaceous Gland Differentiation and Total Elimination of Pelage Follicles

Abstract: Defolliculated is a novel spontaneous mouse mutation that maps to chromosome 11 close to the type I keratin locus. Histology shows abnormal differentiation of the sebaceous gland, with the sebocytes producing little or no sebum and undergoing abnormal cornification. The hair follicles fail to regress during catagen leading to abnormally long follicles. In contrast the hair shafts are shorter than normal, suggesting altered differentiation or proliferation of matrix cells during anagen. The shafts emerge from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 29 publications
2
43
0
Order By: Relevance
“…Hence it is likely that inhibition of BMP signaling in the proximal part of the hair follicle by misexpressed Noggin diverts the normal lineage differentiation of common progenitor cells to the sebocyte lineage rather than hair follicle-type differentiation of hair shaft. Signals that regulate sebocyte development are still poorly understood, 65,66 but this effect is potentially mediated by the Hedgehog (Shh) pathway because BMP suppression by noggin leads to its activation, 31 and Shh signaling increases both size and number of sebaceous glands, including formation of ectopic sebocytes. 67 In summary we have used misexpression of Noggin in hair follicles to inhibit BMP signaling during postnatal hair follicle cycling and shown that this signaling pathway specifically regulates cycling of the nontylotrich hair follicles.…”
Section: Discussionmentioning
confidence: 99%
“…Hence it is likely that inhibition of BMP signaling in the proximal part of the hair follicle by misexpressed Noggin diverts the normal lineage differentiation of common progenitor cells to the sebocyte lineage rather than hair follicle-type differentiation of hair shaft. Signals that regulate sebocyte development are still poorly understood, 65,66 but this effect is potentially mediated by the Hedgehog (Shh) pathway because BMP suppression by noggin leads to its activation, 31 and Shh signaling increases both size and number of sebaceous glands, including formation of ectopic sebocytes. 67 In summary we have used misexpression of Noggin in hair follicles to inhibit BMP signaling during postnatal hair follicle cycling and shown that this signaling pathway specifically regulates cycling of the nontylotrich hair follicles.…”
Section: Discussionmentioning
confidence: 99%
“…22 On the basis of serial histopathologic examinations with disease progression, Sundberg et al have inferred that properly constituted sebum is required for normal desquamation of the inner root sheath and unhindered hair shaft egression; without it, the hair shaft is forced downward, ultimately perforating the hair bulb and inciting reactive inflammation and follicular destruction. 21 It is intriguing that the Defolliculated 23 and Bareskin 24,25 mouse models are phenotypically similar to Asebia but genotypically distinct. Other incompletely characterized mouse models for primary cicatricial alopecia attest to pathogenetic mechanisms that do not appear to depend on primary sebaceous gland pathology.…”
Section: Pathophysiology Of Primary Cicatricial Alopeciamentioning
confidence: 99%
“…Gsdma3 is now known to be the causative gene of not only Rim3 but also several dominant skin mutations in mice, such as Defolliculated (Dfl), Finnegan (Fgn), Bareskin (Bsk), Reduced Coat 2 (Rco2), and Rex-denuded (Re-den). All mutants exhibit hyperproliferation and misdifferentiation of the epidermis, along with abnormal hair follicle development (Lunny et al, 2005;Lyon and Glenister, 1984;Lyon and Zenthon, 1987;Porter et al, 2002;Runkel et al, 2004;Sato et al, 1998;Tanaka et al, 2007). In addition, these studies have suggested that the Gsdm family genes play a critical role in epithelial cell growth and differentiation.…”
mentioning
confidence: 99%